FEASIBILITY STUDY OF UTILIZING SOYBEAN AS AN INTERCROP PLANT IN IMMATURE OIL PALM AS AN EFFORT TO INCREASE THE INCOME OF OIL PALM FARMERS - Dina Arfianti Saragih; Delyana R. Pulungan; Guntoro; Ika Ucha Pradifta Rangkuti; Tifany Zia Aznur; Fadli Akbar Lubis; Juhal Prayogie (RADJA PUBLIKA, 2023)
Land utilization in immature palm oil is very helpful for oil palm farmers to get a source of income when their palm oil crops is still immature. In addition, these intercrops can also be used as ground cover plants, which can prevent erosion and evaporation of the soil. The research was conducted in the experimental garden of the Institut Teknologi Sawit Indonesia (ITSI). The research time was 3 months. The purpose of this research is to determine the feasibility study of soybean business as an intercrop in immature crop land whether or not this soybean crop is profitable. If it is profitable then farmers can receive income from this soybean intercrop before the palm oil plants can be harvested. The results of the research conducted are the production of soybean crops on immature palm oil land with a distance of 20 cm x 20 cm on 2 beds with a bed size of 4 m x 1 m is 10 kg. The total production cost of soybean intercrops in immature palm oil is Rp.86,861. Income on soybean crops in immature palm oil is Rp.130,000. The profit on soybean intercrops in immature oil palm is Rp.43,139. Soybean crops (Grobogan variety) in immature palm oil are financially and economically feasible, with an R/C value > 1, so the farming business is profitable. Break Event Point of soybean intercrops at immature oil palm, BEP production 6.68 kg BEP price Rp.8,686.